PENGINTENSIFAN AKSARA JAWA TERHADAP PENULISAN BAHASA JAWA HURUF LATIN SEBAGAI WAHANA PENDIDIKAN BUDAYA DAN KARAKTER BANGSA - Suyitno Suyitno (Universitas PGRI Semarang, 2015)
Many Latin Javanese writings are incorrect. Those are caused by there is a fact that some Javanese user also use Indonesian in oral and written communication. The problem is faced by language user are: 1) There is the difference of system in language phonetic drawing, and 2) There is similarity definite phonetic.The beginning, the Javanese is written by syllabic Javanese alphabet, while Indonesian is written by phonemic Latin. In Indonesian, the sound [?ëÔÇØ] is drawn by phoneme /o/, while in Javanese the sound is symbolized by phoneme /a/, while /o/ in Javanese is used to symbolize the sound [o].The solution is order to get minimalize Javanese the wrong written which cause to change of meaning, can be done by intensify Javanese letter in Javanese writing, especially for words that possibly have potency of hesitant until hesitancy of meaning can be minimalized.The prime purpose from the matter are planting diciplinen culture, love the country, and care of surroundings. The third values are part which must be developed in education of culture and nation character.